IMPLEMENTASI METODE BRAINSTORMING UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS EKSPLANASI SISWA SMA - Eka Fitriyani; Donny Suharto Kurniawan; Riana Dwi Lestari (IKIP Siliwangi, 2019)
This research is based on the difficulty of writing students through the results of evaluations conducted by the teacher. The problem examined is how is the implementation of the brainstorming method in writing explanatory text? Is the brainstorming method able to improve the results of explanatory text writing? The study was made to find out how the implementation of the brainstorming method in writing explanatory text and to determine the increase in the results of explanatory text writing by the brainstorming method. The researcher used the pre-experimental design method through the one-group-pretest-posttest approach. The research data collection technique was taken from the results of the pretest question sheet and the posttest question sheet that had been done by the students. The sample taken by researchers in class XI was 23 students. the results of the pretest study were 50.00 after the treatment was carried out by applying the brainstorming method, the posttest results increased to 73.33, there was a difference in numbers of 23.33. the increase in the results proved that the implementation of the brainstorming method was very effective in improving explanation text writing skills for high school students.